Learning, uncertainty and central bank activism in an economy with strategic interactions - Martin Ellison; Natacha Valla (European Central Bank (ECB), 2000)
In this paper we examine the optimal level of central bank activism in a standard model of monetary policy with uncertainty, learning and strategic interactions. We calibrate the model using G7 data and find that the presence of strategic interactions between the central bank and private agents creates an additional motivation for caution in optimal monetary policy. An active policy designed to help learning and reduce future uncertainty creates extra volatility in inflation expectations, which is detrimental to welfare.
Keywords: D81; D83; D84; E52; E58; 330